Desarrollo de un biosensor amperométrico de tirosinasa para la determinación de contenido fenólico total en aguas superficiales - Alcaraz, Mirta R. (2012)
Phenolic compounds are presents in environmental fields due to their drainage of the waste water to the superficial waters. They are generated in the production of pesticides, drugs, dyes, plastics and by the petrochemical industries. These compounds are highly toxic and consequently, in order to minimize their hazardous effects it is important to use sensitive and fast techniques for detection and quantitative estimation in environmental samples. Because that, they have been included in the national and international legislations who fix maximum values allowed of phenols in water by using reference methods. The aim of this work is to develop and validate a new analytical methodology based on the use of biosensors to improve the control of toxic residues presents in environmental samples. For this, an amperometric tyrosinase biosensor has been constructed in our laboratory to evaluate the concentration of phenols in superficial waters of the Province of Santa Fe. The enzyme tyrosinase was immobilized on the electrode by means the entrapment of the enzyme with Nafion, being the amount of deposited enzyme 100 UI by electrode. Amperometric experiments were carried out using an electrochemical analyzer. A conventional three electrode system was employed with the enzyme electrode as a working electrode, a platinum wire as the counter electrode, and the Ag|AgCl electrode as a reference electrode. All experiments were performed at the temperature of 30°C, at working potential of -0.100 V in the electrochemical cell containing phosphate buffer at pH=6.80, under constant stirring with magnetic bar. The matrix effect and the presence of interferences were evaluated of each one of samples, and the recovery was studied with a standard addition assay. Five evaluated samples belonging to localities of the north, and south center of Santa Fe presented levels of recovery over 120 %, indicating possible presence of phenols.